RETRACTED: Overexpression of microRNA-216a-3p Accelerates the Inflammatory Response in Cardiomyocytes in Type 2 Diabetes Mellitus by Targeting IFN-α2 - Liu, Xiaomeng; Zhang, Yusong; Liang, Hongwei; Xu, Yanchao (Frontiers in Endocrinology, 2020)
Background: Type 2 diabetes mellitus (T2DM) is a chronic, hyperglycemia-associated, metabolic disorder. Heart disease is a major complication of T2DM. The present study aimed to explore the effects of miR-216a-3p on cardiomyocyte proliferation, apoptosis, and inflammation in T2DM through the Toll-like receptor (TLR) pathway involving interferon-α2 (IFN-α2) mediation. Methods: T2DM was induced in rats by a high-fat diet, in combination with an intraperitoneal injection of low-dose streptozotocin. ELISAs were conducted to measure inflammatory-related factors in serum. Next, isolated cardiomyocytes were used in loss- and gain-of-function experiments, followed by MTT and flow cytometry assays, conducted to evaluate cell proliferation, cell cycle, and apoptosis. Results: Our results revealed an increase in the inflammatory response in T2DM rat models, accompanied by significantly increased expression of miR-216a-3p and TLR pathway-related genes. However, a decrease in the expression of IFN-α2 was observed. Moreover, the presence of an miR-216a-3p inhibitor and si-IFN-α2 increased the expression of TLR pathway-related genes and cell apoptosis, whereas cell proliferation was significantly decreased in the cardiomyocytes. Conclusion: We found that in T2DM, miR-216a-3p inhibited the proliferation and enhanced the apoptosis of cardiomyocytes and generated an inflammatory response through activation of the TLR pathway and targeting of IFN-α2.